Non-Symmetrical Selective Harmonic Elimination PWM Techniques: The Unipolar Waveform - Dahidah, Mohamed S. A.; Agelidis, Vassilios G. (2007)
Selective harmonic elimination pulse-width modulation (SHE-PWM) techniques offer a tight control of the harmonic spectrum of a given voltage waveform generated by a power electronic converter along with a low number of switching transitions. These optimal switching transitions can be calculated through Fourier theory, and for a number of years quarter-wave and half-wave symmetries have been assumed when formulating the problem. It is shown recently that symmetry requirements can be relaxed as a constraint. This changes the way the problem is formulated and different solutions can be found. This paper reports solutions to the switching transitions of unipolar SHE-PWM when both the quarter- and half-wave symmetries are abolished. Various operating points for both single- and three-phase patterns and different values of the modulation index are reported. Selected simulation and experimentally verified results are reported to show the effectiveness of the proposed method.